2018
DOI: 10.5114/pg.2018.78343
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the management of irritable bowel syndrome

Abstract: These guidelines constitute an update of the previous “Recommendations on the management of irritable bowel syndrome” issued in 2008. They have been developed by a Task Force organized by the Governing Board of the Polish Society of Gastroenterology. They discuss, with particular emphasis on new scientific data covering papers published since 2008, the aetiology, epidemiology, clinical presentation, diagnostic principles and criteria for the diagnosis, and recommendations for the treatment of irritable bowel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 220 publications
3
76
0
15
Order By: Relevance
“…Of note, we found some papers (N = 15) that covered IBS therapeutic approaches where probiotics were recommended/evaluated as a highly recommended treatment option, but the authors of the different studies examined different IBS subtypes as mixtures or did not report on improved intestinal transit time/bowel movements frequency/stool consistency [75,87,90,[93][94][95][96][97][98][99][100][101][102][103][104]. These documents were not placed in Tables II-IV. Overall, there seemed to be an agreement that probiotics may improve intestinal motility, but medical authorities predominantly recommended probiotics as an integral part of treatment for constipation cautiously.…”
Section: Results Of Systematic Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we found some papers (N = 15) that covered IBS therapeutic approaches where probiotics were recommended/evaluated as a highly recommended treatment option, but the authors of the different studies examined different IBS subtypes as mixtures or did not report on improved intestinal transit time/bowel movements frequency/stool consistency [75,87,90,[93][94][95][96][97][98][99][100][101][102][103][104]. These documents were not placed in Tables II-IV. Overall, there seemed to be an agreement that probiotics may improve intestinal motility, but medical authorities predominantly recommended probiotics as an integral part of treatment for constipation cautiously.…”
Section: Results Of Systematic Searchmentioning
confidence: 99%
“…Probiotics contain live microorganisms, which when administered in adequate amounts confer a health benefit to the host [74]. Probiotics have been used successfully in patients with various FGIDs, and some recommendations concerning use of probiotics in clinical practice are already available [9,75]. However, their use in constipated individuals is still controversial.…”
Section: Probiotics In Cic Treatmentmentioning
confidence: 99%
“…A systematic review found no beneficial effect with fibers, whereas meta-analysis including 906 patients showed that soluble fibers intake helps alleviate the symptoms. [18] Furthermore, dietary fiber has also other benefits. It improves body weight management, regulates blood pressure and lower blood cholesterol levels.…”
Section: Fibermentioning
confidence: 99%
“…Main purpose is to encourage the intake of foods that individually have beneficial effects and the avoidance of unhealthy options. [18] Moreover, introducing to everyday diet foods that alleviate symptoms have to be safe and well tested.…”
Section: Recommended Foodsmentioning
confidence: 99%
See 1 more Smart Citation